Evolution of high-frequency Raman modes and their doping dependence in twisted bilayer MoS2. Issue 33 (13th May 2020) - Debnath, Rahul; Maity, Indrajit; Biswas, Rabindra; Raghunathan, Varun; Jain, Manish; Ghosh, Arindam
Abstract : Here, we demonstrate the systematic evolution of the interlayer coupling and electron-phonon coupling strength with twist angle in bilayer MoS2 using a combination of Raman spectroscopy and a combination of classical and first-principles based simulations. Abstract : Twisted van der Waals heterostructures provide a new platform for studying strongly correlated quantum phases. The interlayer coupling in these heterostructures is sensitive to the twist angle ( θ ) and key to controllably tuning several interesting properties. Here, we demonstrate the systematic evolution of the interlayer coupling strength with twist angle in bilayer MoS2 using a combination of Raman spectroscopy and classical simulations. At zero doping, we observe a monotonic increase in the separation between the A1g and E2g 1 mode frequencies as θ decreases from 10° → 1°, and the separation approaches that of a bilayer at small twist angles. Furthermore, using doping dependent Raman spectroscopy, we reveal the θ dependent softening and broadening of the A1g mode, whereas the E2g 1 mode remains unaffected. Using first principles based simulations, we demonstrate large (weak) electron–phonon coupling for the A1g (E2g 1 ) mode, which explains the experimentally observed trends. Our study provides a non-destructive way to characterize the twist angle and the interlayer coupling and establishes the manipulation of phonons in twisted bilayer MoS2 (twistnonics).